A systems thinking approach for examining the turning points in the Finnish public sport policy - Lehtonen, Kati; Uusikylä, Petri; Jalonen, Harri; Lappalainen, Sari (Frontiers in Sports and Active Living, 2025)
Background and study aimThis study proposes a longitudinal analysis of the Finnish public sports policy and explores the dynamics between turning points from a systems thinking perspective. We argue that a better understanding of the dynamics and relationships between turning points, interruptions, and new paths in the policy process can guide future options for public sports policies.Material and methodsDocumentary and interview-based materials were used as data and timeline mapping as an analyzing method.ResultsOur results show that there have been four turning points during the review period. The first turning point in the early 1990s is fundamental and it had large-scale effects on the direction of sport policy. The other three are moderate in their nature, smoothly affecting the direction of the policy process. Policy venues have changed from theme-specific working groups to permanent entities operating within the state administration. At the same time, party politics has returned to politics, a phenomenon that seems at odds with the first turning point.ConclusionsFor decision-makers and practitioners, the current policy space requires increasing ability to make decisions on a long-term basis despite several interests, increasing complexity of governance and the needs of differentiated subsystems.